Pelatihan Pembuatan Akun Grabfood Sebagai Upaya Meningkatkan Penjualan UMKM Bubur Cianjur Bapak Qodir di Kedung Waringin Bogor: Pengabdian - Fujiyati; Cucu Sumartini, Lilis; Sujana, Ujang; Wisnu Nugroho, Haris (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mr. Qodir's Cianjur Porridge UMKM is located on Jl.KH.M.Mukhtar No. 68 Kedung Waringin , Bojong Gede, Bogor Regency is a culinary business that sells culinary products in the form of Cianjur chicken porridge. In running his business, he has been relying on conventional sales where buyers come directly to the place of sale. Even though in the current digital era, E-commerce has been widely used for businesses in increasing sales. The result of this community service socialization is expected to increase the sales of Mr. Qodir's Cianjur Chicken Porridge through the implementation of the Grabfood application so that it can reach a wider range of customers and can optimize the ordering and delivery process. The use of the Grabfood application can be an effective alternative in increasing business competitiveness in today's digital era.